2020
DOI: 10.1111/psyp.13621
|View full text |Cite
|
Sign up to set email alerts
|

Brain responses to change in phonological structures of varying complexity in children and adults

Abstract: Language-related change-detection processes are often investigated using syllables that are very simple in terms of phonological structure. However, phonological complexity is known to be challenging for young typically developing children and pathological populations. We investigated brain correlates of phonological processing and their age-related changes with a passive change-detection protocol including stimuli of varying phonological complexity, which allowed comparing responses to simple and complex phon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 77 publications
(148 reference statements)
0
7
0
Order By: Relevance
“…This notion was further strengthened by similar results obtained by Liu et al (2014) with consonant and lexical tone contrasts in pre‐school and school‐aged Mandarin speaking children. David et al (2020) also reported a larger LDN in children with respect to adults, elicited by phonologically complex rather than simple multisyllabic non‐words. Although this transfer mechanism for regularities could be relevant for language learning, our findings together with previous studies (Zachau et al, 2005) suggest that it is not necessarily language‐specific.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This notion was further strengthened by similar results obtained by Liu et al (2014) with consonant and lexical tone contrasts in pre‐school and school‐aged Mandarin speaking children. David et al (2020) also reported a larger LDN in children with respect to adults, elicited by phonologically complex rather than simple multisyllabic non‐words. Although this transfer mechanism for regularities could be relevant for language learning, our findings together with previous studies (Zachau et al, 2005) suggest that it is not necessarily language‐specific.…”
Section: Discussionmentioning
confidence: 93%
“…This component was tentatively identified as the late discriminative negativity (LDN), which was also reported in another study encompassing the abstract‐feature paradigm as “Late MMN” (Zachau et al, 2005). Previous studies that used the canonical oddball paradigm reported the presence of this component over different time windows scattered across the 350–600 ms interval (Choudhury et al, 2015; David et al, 2020; Honbolygó et al, 2017). Given the absence of a priori hypotheses on its presence and/or modulation, the analysis of this component must be considered explorative.…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…Several studies have measured the late discriminative negativity (LDN) that follows the MMN and have found that the latency overlaps with the N5 (Honbolygó et al, 2017; Peter et al, 2012). Although the LDN is considered to reflect cognitive‐level processing of deviant stimuli (Čeponiene et al, 2004), its functional significance remains unclear (David et al, 2020). It is necessary to closely examine the functional significance of the late negativities elicited by music‐syntactic irregularities and acoustic irregularities in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Along with MMN, an additional negativity, the late discriminative negativity (LDN), was observed in our study. The LDN is a recently established component found in oddball paradigms and serves as an index of phonological discriminative abilities (Hill et al, 2004;Horváth et al, 2009;Jakoby et al, 2011;David et al, 2020). Similar to the MMN, the LDN is also an automatic response associated with higher cognitive processes and may represent the recruitment of additional cortical resources needed to extract the phonological differences between the standard and deviant stimulus and form phonological representations (Shestakova et al, 2003;Hill et al, 2004;Zachau et al, 2005;Barry et al, 2009).…”
Section: Placementioning
confidence: 99%